On correcting measurement error in the persistence rate estimator. Issue 4 (21st April 2018) - Feng, Cindy X.; Piesse, Andrea
Abstract: In the field of education, it is often of great interest to estimate the percentage of students who start out in the top test quantile at time 1 and who remain there at time 2, which is termed as "persistence rate, " to measure the students' academic growth. One common difficulty is that students' performance may be subject to measurement errors. We therefore considered a correlation calibration method and the simulation–extrapolation (SIMEX) method for correcting the measurement errors. Simulation studies are presented to compare various measurement error correction methods in estimating the persistence rate.